Agronomic performance of wheat cultivars for off-season in the Santa Catarina Plateau, Brazil - Fioreze, Samuel Luiz; Oliveira, James Cruz; Mazzuco, Volni; Wuaden, Ana Flávia; Drun, Robson Pelissari (Revista de Ciências Agroveterinárias, 2020)
The increase in Brazilian wheat production to supply the domestic demand is associated with the increase of the cultivated area in historically unexplored regions or seasons. In this sense, this paper aimed to study the yield performance of wheat cultivars in off-season conditions in the Santa Catarina Plateau, in the state of Santa Catarina, Brazil. The field experiment was carried out from February to June 2018. Five wheat cultivars (BRS 264, BRS 394, BRS Parrudo, Tbio Audaz, and Tbio Sonic) were sown on February 14th and March 1st. The morphological parameters of the plants were determined at the anthesis stage. Production components and grain productivity were determined at the maturation stage. In addition, the duration of the period between emergence and flowering and between flowering and maturation was determined. The ‘BRS Parrudo’ cultivar did not develop satisfactorily for off-season cropping, showing anomalies on cob formation. The remaining cultivars studied presented satisfactory growth and grain yield when sown on February 14th.